Seco-pimarane diterpenoids and androstane steroids from an endophytic Nodulisporium fungus derived from Cyclosorus parasiticus. (June 2023) - Yang, Xiaoli; Wu, Ping; Xue, Jinghua; Li, Hanxiang; Wei, Xiaoyi
Abstract: Five previously undescribed specialized metabolites, including three 9, 11- seco -pimarane diterpenoids, nodulisporenones A–C, and two androstane steroids, nodulisporisterones A and B, together with previously described ergosterol derivatives, dankasterone A and demethylincisterol A3, were isolated from solid cultures of the endophytic fungus Nodulisporium sp. SC-J597. Their structures including absolute configurations were elucidated by extensive spectroscopic analysis and theoretical calculations of electronic circular dichroism spectra. Among them, nodulisporenones A and B are the first examples of seco -pimarane diterpenoids that is cyclized to form an unprecedented diterpenoid lactone scaffold and nodulisporisterones A and B represent the first normal C19 androstane steroids of fungal origin. Nodulisporisterone B exhibited potent inhibitory effect on the production of NO in LPS-stimulated RAW264.7 macrophages (IC50 = 2.95 μM). This compound, together with the two known ergosterol derivatives, also displayed cytotoxicity against A549, HeLa, HepG2 and MCF-7 cancer cell lines with IC50 values of 5.2–16.9 μM. Graphical abstract: Seco-pimarane diterpenoids, nodulisporenones A–C, and androstane steroids, nodulisporisterones A and B, were isolated from a Cyclosorus parasiticus leaf-derived Nodulisporium fungus. Nodulisporisterone B was active against the tested cancer cells and inhibited NO production in LPS-stimulated RAW264.7 macrophages. Image 1 Highlights: Five seco-pimarane diterpenes and androstane steroids were isolated from Nodulisporium sp. Two seco-pimarane diterpenes had an unprecedented diterpenoid lactone scaffold. Normal androstane steroids were isolated from a fungal source for the first time. One of the steroids was active against cancer cells and inhibited NO production in RAW264.7 cells.